Broadway and economics : economic lessons from show tunes - Rousu, Matthew C.; Taylor and Francis (Boca Raton, FL : Routledge, an imprint of Taylor and Francis, 2018)
Economics has often been described as "the dismal science," with TV and movies reinforcing this description. However, economics is a powerful tool that can be used to understand how the world works, helping to answer confusing puzzles and solve the world s problems. Surprisingly, Broadway musicals are an excellent way to show this.Featuring classic songs from some of the most popular shows ever produced, along with some hidden gems, Broadway and Economics will be of interest to anybody studying an introductory economics course as well as theatre aficionados.Musicals tell engaging stories through song and many are rich with economic concepts. This book analyzes 161 songs from 90 musicals to explore what they can teach us about supply and demand, monetary policy and numerous other core economic concepts. While some songs have an obvious connection to economics, other connections may seem less apparent. When you hear "Let it Go" from Frozen, does your mind think about a firm s production decisions? After reading this book, it will. Whether showing how Hamilton can illustrate concepts of central banking, or how "Stars" from Les Miserables provides a perfect example of inelastic demand, the author presents complicated topics in an understandable and entertaining way.
chapter 1776 1776 -- chapter A Funny Thing Happened on the Way to the Forum -- chapter A Gentleman s Guide to Love and Murder -- chapter Annie -- chapter Annie Get Your Gun -- chapter Anyone Can Whistle -- chapter Avenue Q -- chapter Beauty and the Beast -- chapter Big Fish -- chapter Billy Elliot -- chapter Bonnie and Clyde -- chapter Cabaret -- chapter Candide -- chapter Carousel -- chapter Chicago -- chapter Cinderella -- chapter Closer than Ever -- chapter Curtains the Musical -- chapter Dames at Sea -- chapter Dear World -- chapter Dirty Rotten Scoundrels -- chapter Do I Hear a Waltz? -- chapter Evita -- chapter Fiddler on the Roof -- chapter Frozen -- chapter Follies -- chapter Fun Home -- chapter Grease -- chapter Gypsy -- chapter Hamilton -- chapter Hands on a Hardbody -- chapter Happy End -- chapter Heathers the Musical -- chapter Hedwig and the Angry Inch -- chapter Hello Dolly -- chapter Honeymoon in Vegas -- chapter How to Succeed in Business without Really Trying -- chapter I I Can Get it For You Wholesale -- chapter If/Then -- chapter In the Heights -- chapter Inside U.S.A. -- chapter Joseph and the Amazing Technicolor Dreamcoat -- chapter Kinky Boots -- chapter Kiss Me Kate -- chapter La La Land -- chapter Legally Blonde -- chapter Les Misérables -- chapter Little Shop of Horrors -- chapter Made in Dagenham -- chapter Mamma Mia -- chapter Mary Poppins -- chapter Matilda -- chapter Moana -- chapter Newsies -- chapter Oliver! -- chapter On the Twentieth Century -- chapter Once on This Island -- chapter 1 One Man, Two Guvnors -- chapter Pacific Overtures -- chapter Phantom of the Opera -- chapter Pippin -- chapter Ragtime -- chapter Rent -- chapter School of Rock -- chapter She Loves Me -- chapter Shrek the Musical -- chapter Something Rotten -- chapter Sunday in the Park with George -- chapter Sunny Afternoon -- chapter Sunset Boulevard -- chapter 10 Tenderloin -- chapter The Addams Family -- chapter The Bridges of Madison County -- chapter The Fix -- chapter The Full Monty -- chapter The Last Five Years -- chapter The Last Ship -- chapter The Lion King -- chapter The Little Mermaid -- chapter The Music Man -- chapter The Pajama Game -- chapter The Producers -- chapter The Rothschilds -- chapter The Sound of Music -- chapter The Wedding Singer -- chapter Thoroughly Modern Millie -- chapter Tovarich -- chapter Urinetown -- chapter Working -- chapter You re a Good Man Charlie Brown -- chapter Notes -- chapter Song Reference Table.
Keywords: Economics; BUSINESS & ECONOMICS / Economics / General; BUSINESS & ECONOMICS / Reference; Broadway; Broadway Musicals; Economics; Economics And Broadway; Economics And Popular Culture; Musicals; Popular Culture; Showtunes; Economics -- Case studies; Musicals -- Economic aspects -- Case studies